An innovative, integrated, and community based MBBS Curriculum: a humanistic and holistic approach for Karnali Academy of Health Sciences - Amgain, Kapil; Budhathoki, S. (Journal of Karnali Academy of Health Sciences, 2018)
Background: With the mission of providing easy and accessible health services/facilities for the people of backward areas by producing qualified and skillful health professionals, Karnali Academy of Health Sciences (KAHS) has been established in 2011, by an Act of parliament of Nepal. In the way of fulfilling its mission, PCL nursing program (2014), PCL in General Medicine (2015), Bachelor in Public Health (2018) and Bachelor in Midwifery Sciences (2018) programs have already started successfully; and next goal of our Academy is to start MDGP and MBBS in near future. In this context of its academic progress, KAHS is developing an ideal MBBS curriculum by introducing the recent innovation in the field of medical education. Method: This was the cross-sectional study conducting among 100 public, 50 medical students and 20 professors and faculties of TU, KU, PAHS and BPKIHS from June, 2018 to November, 2018. The data were collected with the help of three different set of semi-structured questionnaires. Moreover, we had gone through the MBBS curriculum of 10 Universities/Academy, and the data regarding the type of curricular strategies, credit hours and course contents of individual subject, academic calendar, schedule of community posting, and evaluation pattern were collect in the performa. The collected data were analyzed and presented in the tables. Result: Present study found that out of 100 participants, almost all of the participants felt the need of one medical college and a well facilitated hospital in Karnali Province, especially in Jumla, with the qualified, skillful, patient-friendly medical doctors as well as other health professionals. After interviewed with the professors and faculties of various universities, we found that the integrated, community based and student centered curriculum had better level of understanding than the discipline based, teacher-centered MBBS curriculum. Out of the four prevailing MBBS curricula (TU, KU, PAHS and BPKIHS) in Nepal, all curricula incorporated the horizontal integration approach in basic sciences with early pre-clinical exposure and community posting. In addition to this, integrated MBBS curriculum of PAHS was fully problem-based, and community based. Conclusion: Integrated, student-centered, community based, problem based as well as problem oriented innovative teaching-learning method outweigh the contemporary teacher-centered hospital-based learning in medical education. So, we would like to recommend the development of integrated MBBS curriculum based on the organ system for the proper implementation recent innovation of medical education.